FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK SECARA SUKARELA - Lumbantobing, Yuvita Chantri; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2015)
The  reseacrh  aims  to  knows  empirical  evidence  all  factors  influencing  auditor  switching  on company sector non finance listed in Indonesia Stock Exchange in 2008-2013 period. The determinant factors are analysized using many proxy such as CEO turnover (CEO), audit opinion (OPINI), clients size (LnTA), financial distress (DER) and company growth(∆S). The population of this research is company sector non finance which is listed in “Bursa Efek Indonesia” (BEI) during period 2008-2013. Sampling is conducted based on method which used in this research is method purposive sampling, that based in criteria has been determined research hypothesis are tested by logistic regression analytical method. Result indicates that variables which have significantly  effect to  the voluntary  auditor  switching  is  only  client size.  Variables like  CEO turnover, audit opinion, financial distress and company growth have no significant effect to voluntary auditor switching.